Altered resting‐state functional connectivity between subregions in the thalamus and cortex in migraine without aura. (16th July 2020) - Qin, Z. X.; Su, J. J.; He, X. W.; Zhu, Q.; Cui, Y. Y.; Zhang, J. L.; Wang, M. X.; Gao, T. T.; Tang, W.; Hu, Y.; Liu, Y. S.; Qiao, Y.; et al.
Abstract : Background and purpose: Migraine is a complex and disabling neurological disorder, the exact neurological mechanisms of which remain unclear. The thalamus is considered to be the hub of the central processing and integration of nociceptive information, as well as the modulation of these processes. Methods: A total of 48 migraineurs without aura (MWoAs) during the interictal phase and 48 age‐ and sex‐matched healthy controls underwent resting‐state functional magnetic resonance imaging scans. We utilized masked independent component analysis and seed‐based functional connectivity (FC) to investigate whether MWoAs exhibited abnormal FC between subregions in the thalamus and the cortex regions. Results: The MWoAs showed significantly weaker FC between the anterior dorsal thalamic nucleus and left precuneus. Additionally, MWoAs exhibited significantly reduced FC between the ventral posterior nucleus (VPN) and left precuneus, right inferior parietal lobule (R‐IPL) and right middle frontal gyrus. Furthermore, the FC Z‐scores between the VPN and R‐IPL were negatively correlated with pain intensity in MWoAs. The disease duration of patients was negatively correlated with the FC Z‐scores between the VPN and R‐IPL. Conclusion: These altered thalamocortical connectivity patterns may contribute to multisensory integration abnormalities, deficits in pain attention, cognitive evaluation and pain modulation. Pain sensitivity and disease duration are closely tied to abnormal FC between the VPN and R‐IPL. Remarkably, recurrent headache attacks might contribute to this maladaptive functional plasticity closely related to pain intensity.